High Moesin Expression Is a Predictor of Poor Prognosis of Breast Cancer: Evidence From a Systematic Review With Meta-Analysis - Hu, Xiaoli; Liu, Yang; Bing, Zhitong; Ye, Qian; Li, Chengcheng (Frontiers in Oncology, 2021)
Owing to metastases and drug resistance, the prognosis of breast cancer is still dismal. Therefore, it is necessary to find new prognostic markers to improve the efficacy of breast cancer. Literature shows a controversy between moesin (MSN) expression and the prognosis in breast cancer. Here, we aimed to conduct a systematic review and meta-analysis to evaluate the prognostic relationship between MSN and breast cancer. Literature retrieval was conducted in the following databases: PubMed, Web of Science, Embase, and Cochrane. Two reviewers independently performed the studies screening and data extraction. Gene Expression Omnibus (GEO) database including both breast cancer gene expression and follow up datasets were selected to verify literature results. R software was employed for the meta-analysis. A total of 9 articles with 3443 patients and 16 datasets with 2916 patients were ultimately included. Results indicated that there was a significant relationship between MSN and lymph node metastases (P<0.05), and high MSN expression was associated with poor outcome of breast cancer patients (HR=1.99; 95% CI 1.73-2.24). In summary, there is available evidence to support that high MSN expression has valuable importance for the poor prognosis in breast cancer patients.